Initial Experience of Totally Tubeless Ultra-Mini Percutaneous Nephrolithotomy - Rakib, Md Abdur; Islam, Md Shahidul; Waheed, SM Shameem; Chwdhury, Md Ashif; Alam, Mohammad Shafiul; Rashid, Mohammad Harun or (Bangladesh Journal of Urology, 2022)
Objectives : The Objectives of this study is to determine the outcome and effectiveness of Ultra-mini percutaneous nephrolithotomy (PCNL) for treating low-volume renal stone without placement of any stent and nephrostomy tube as a supplement to the conventional PCNL. Material and methods: The Patients who underwent ultra-mini PCNL bwtween July 2018 to December 2018. were studied.This was a prospective study of 14 patients.This study was carried out in urology centre of CMH Dhaka.Before the study ethical clearance was taken from hospital ethical committee. All these patients had their first-line treatment. The patients had calculus limited to either a single calyx or just extending to the pelvis and the stone size was less than 1.5 cm in its maximal dimension. The mean stone size was 10.8+_4.2(5-15mm). An 6 Fr operating nephroscope was used. The patients were placed in prone position. The stones were fragmented using Holmium-YAG laser. Various surgical outcomes including duration of the surgery, stone-free rate and any subsequent complications-if any-were analyzed.The stone free rate was assessed on the 1st day and at three month after surgery by X-ray KUB and ultrasonography. Results: The study includes a series of 14 patients (one patient treated with bilateral renal stone disease). The mean age of the patients was 39.07 years and body mass index was 25.5 kg/m2. Intrarenal stone location was as follows: lower calyx, n=7; middle calyx, n=3, upper calyx, n=1, and pelvis, n=3. Median operative time was 52.66 min (range: 40–65) and the stone-free rate was 93.3% at first day and 97% after three month follow up.. Only one patient had residual fragments and needed subsequent extracorporeal shock wave lithotripsy. Conclusion: Ultra-mini PCNL in prone position with a complete tubeless approach for renal stone disease is a safe method for treating low-volume stone disease. A long term large scale multicentre study may be required to validate this technique. Bangladesh J. Urol. 2021; 24(2): 118-123